IDENTIFIKASI JAMUR Aspergillus sp. PADA KACANG TANAH (Arachis hypogaea L) YANG DIJUAL DI PASAR YOUTEFA KOTA JAYAPURA PAPUA - Ester Rampa; Beatrice Patiung; Herlando Sinaga (Jurnal Biogenerasi, 2022)
Research has been carried out with the title "Identification of Aspergillus sp. On Peanuts (Arachis hypogaea L) which are sold in Youtefa Market, Jayapura City”. The research was carried out at the Microbiology Laboratory of the Faculty of Mathematics and Natural Sciences, Cendrawasih University, from January 9, 2021 to April 9, 2021. The purpose of this study was to determine whether there was contamination of the fungus Aspergillus sp. on peanuts circulating in Youtefa Market, Jayapura city. This type of research is descriptive research with laboratory experiments. The population in this study were all peanuts (Arachis hypogaea L) which were sold at Youtefa Market, Jayapura city. The samples used in this study were peanuts (Arachis hypogaea L) in 5 different places each weighing 100 grams which were sold at the Youtefa market, and the samples were taken randomly. Isolation of Aspergillus sp. It was carried out by pouring cup method on PDA media, then macroscopic identification and microscopic identification were carried out. The results showed that samples of peanuts from 2 different types, namely 5 samples of dark brown peanuts were positive for contamination with the fungus Aspergillus sp. and 5 samples of brownish white peanuts were positive for Aspergillus sp. And Penicillium sp.